PENDAMPINGAN SUAMI DAN SKALA NYERI PADA PERSALINAN KALA 1 FASE AKTIF - Yuliastanti, Triani; Nurhidayati, Novita (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2013)
Companion on maternal influence because it can do much to assist the mother during labor and to provide care, safety, comfort, encouragement, reassuring the mother, reducing maternal stress or emotional atatus be better so as to shorten the labor process The purpose of this study was to determine empirically mentoring relationship with the husband on a pain scale of phase 1 of the active phase of labor in BPS Siti Lestari Amd, Keb. Methods This study was an observational analytic study using cross sectional method. The population in this study were all mothers inpartu 1 active phase when delivered in BPS Siti Lestari Sumomorodukuh Plupuh Sragen, with 32 respondents. Chi Square analysis of the data. Research results indicate that the relationship between mentoring There husband with a pain scale at the active stage of labor the mother in a phase 1 BPS Siti Lestari Sumomorodukuh Plupuh Sragen with test results X²count >X2table( 8.381>5,99) and p value = 0.015 (p <0,05). The conclusion of this study is the husband on maternal assistance when one phase is active in BPS Siti Lestari Amd, Keb had a significant association with the reduction of pain during childbirth. Keyword: Husband mentoring, labor pain